Quick Recovery of Fulminant Hepatitis E Virus (HEV) Infection in Few Days with Excessive Intake of Plum Juice During Last Trimester of Pregnancy - Braira Wahid, Anam Amir, Haris Abdul Rehman, Mehreen Fatima, Ayesha Ameen, Aamna Syed, Hafiz Khawar, Muhammad Nauman Aziz (Pakistan Journal of Medical & Health Sciences, 2022)
Hepatitis E virus (HEV) is the cause of acute viral hepatitis and fulminant hepatic failure. HEV has huge global bioburden which accounts for 70,000 deaths and 20 million infections per year. HEV during third trimester of pregnancy causes maternal death, fulminant hepatitis, and death of fetus in some cases. Existing literature suggest 33% prevalence of vertical transmission among females infected with HEV during third trimester of their pregnancy. This case-study presents an unusual quick recovery of fulminant HEV in a pregnant female with no medication and excessive intake of plum juice during third trimester followed by normal delivery of health child. Further studies should be conducted to understand the effects of plum juice on liver function and its metabolism. Keyword: fulminant HEV, Pakistan, treatment, pregnant